APPLYING THE THEORY OF CONSTRAINTS TO INCREASE ECONOMIC VALUE ADDED: PART 2 - Smith, M.; Pretorius, P. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This article describes a way to implement the holistic approach of the Theory of Constraints (TOC) which will lead to an increase in the Economic Value Added (EVA) of a business. The approach consists of two parts: the adoption of the holistic approach, and the implementation of a new company strategy. The pitfalls in implementing a holistic approach are discussed. The elements of a company strategy that is compatible with the holistic approach are described. AFRIKAANSE OPSOMMING: Hierdie artikel beskryf